Burnout in Portuguese physiotherapists during COVID‐19 pandemic. (26th May 2021) - Jácome, Cristina; Seixas, Adérito; Serrão, Carla; Teixeira, Andreia; Castro, Luísa; Duarte, Ivone
Abstract: Objective: This study described the burnout experienced by physiotherapists during the COVID‐19 pandemic and analysed the role of possible factors of this occupational phenomenon. Methods: Cross‐sectional study based on a web‐based survey applied to physiotherapists living in Portugal. The survey included sociodemographic, health status and clinical practice questions. The Copenhagen Burnout Inventory (personal, work‐ and patient‐related burnout), the Resilience Scale, the Depression Anxiety and Stress Scales and the Satisfaction with Life Scale were used. Results: A total of 511 physiotherapists (median 33 years old, 82% females) completed the survey. The participants worked mainly in private practice (50%) and wards (35%). During COVID‐19, 52% were working directly with patients, but only 18% were working with COVID‐19 patients. Personal (42%), work‐ (42%) and patient‐related burnout (25%) was observed. Three significant models explained personal‐ ( R 2  = 51%), work‐ ( R 2  = 31%) and patient‐related burnout ( R 2  = 16%). Lower levels of resilience and higher levels of depression and stress were significantly associated with personal, work‐ and patient‐related burnout. Being female and working directly with patients were additionally associated with both personal and work‐related burnout. Having health problems and working with COVID‐19 patients were only associated with personal burnout. Conclusions: More than 40% of physiotherapists experienced personal and work‐related burnout and 25% patient‐related burnout, with resilience, depression and stress having a relevant role in the three burnout dimensions. Early detection and management strategies need to be implemented to address physiotherapists' physical and psychological fatigue and exhaustion.